"Strategic sequences" in adipose‐derived stem cell nerve regeneration. Issue 4 (27th December 2013) - Widgerow, Alan D.; Salibian, Ara A.; Kohan, Emil; Sartiniferreira, Tadeu; Afzel, Hassaan; Tham, Thanh; Evans, Gregory R.D.
<x xml:space="preserve">Abstract</x> Background Peripheral nerve injuries (PNI) are a major source of morbidity worldwide. The development of cellular regenerative therapies has the potential to improve outcomes of nerve injuries. However, an ideal therapy has yet to be found. The purpose of this study is to examine the current literature key points of regenerative techniques using human adipose‐derived stem cells (hADSCs) for nerve regeneration and derive a comprehensive approach to hADSC therapy for PNI. Methods A literature review was conducted using the electronic database PubMed to search for current experimental approaches to repairing PNI using hADSCs. Key search elements focused on specific components of nerve regeneration paradigms, including (1) support cells, (2) scaffolds, and (3) nerve conduits. Results Strategic sequences were developed by optimizing the components of different experimental regenerative therapies. These sequences focus on priming hADSCs within a specialized growth medium, a hydrogel matrix base, and a collagen nerve conduit to achieve neuromodulatory nerve regeneration. hADSCs may exert their neuroregenerative influence through paracrine effects on surrounding Schwann cells in addition to physical interactions with injured tissue. Conclusions hADSCs may play a key role in nerve regeneration by acting primarily as support for local neurotrophic mediation and modulation of nerve growth rather than that of a primary neuronal differentiation agent. © 2013 Wiley Periodicals, Inc. Microsurgery 34:324–330, 2014.